Avaliação do cortisol, dehidroepiandrosterona sulfato e dos perfis lipídico e imunológico e suas correlações com a sensibilidade dolorosa, depressão e funcionalidade em mulheres com fibromialgia na pós-menopausa - Freitas, Rodrigo Pegado de Abreu (2009)
Fibromyalgia (FM) is a non-inflammatory rheumatic syndrome characterized by widespread musculoskeletal pain with palpable tender points, muscle stiffness, fatigue, and sleep disturbances. Patients with FM have hormonal changes that are directly correlated with symptoms of the syndrome. The neuroendocrine regulation may be impaired, with abnormalities in the hypothalamus-pituitary-adrenal (HPA) axis with various hormones showing changes in their levels. In women in fertile period, various gonadal hormones are associated with symptoms of the syndrome, but studies focusing only a population of women in post-menopausal period who do not use hormone replacement are rare. We developed an analytical cross sectional study to assess the plasma levels of cortisol and dehidroepiandrosterona sulfate (DHEA-S) with quimioluminescence method in a group of 17 women with FM and 19 healthy women in post-menopause who do not use hormone replacement and observe the correlation with the symptoms of pain through algometry, depression and physical functional capacity measured from the Beck Depression Index (BDI) and the Fibromyalgia Impact Questionnaire (FIQ). Three blood samples were collected in the morning (between 8:00 9:30) with an interval of 24 hours for the measurements of hormonal levels and biochemical profile. There were no immunological or lipid changes in patients with FM. Comparing the two groups, there is no difference in levels of cortisol and a tangential effect for DHEA-S (p=0,094) with the lowest levels in the FM. DHEA-S also correlated with pain threshold (r=0,7) and tolerance (r=0,65) in group FM. We found the presence of depressive state and low physical functional capacity in FM. It was also evident that women in post-menopausal period, DHEA-S should influence the symptoms of increased sensitivity to pain, but not the presence of depressive status and low physical functional